Pengaruh Persepsi Pasien tentang Faktor-Faktor Pelayanan Profesionalisme terhadap Minat Kunjungan Lanjut di Rumah Sakit - Haqi, Gibraltar Kasyiful; Syaodih, Erliany; Syarifuddin, Didin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to analyze the influence of patient perceptions regarding professionalism service factors on their intention to revisit hospitals. The study highlights the strategic importance of professional healthcare services in determining patient satisfaction and loyalty. The examined factors include the competence of medical personnel, doctor-patient communication, nurse empathy, and the comfort of hospital facilities. The study employed a quantitative survey method involving 200 outpatients from RS Prima Medika Pemalang. Data were gathered using a Likert-scale questionnaire and analyzed through Structural Equation Modeling (SEM) to test five hypothesized relationships between service dimensions and revisit intention. The results show that patient perceptions of service professionalism significantly influence their revisit intention. This research contributes to hospital management strategies in improving service quality and fostering patient loyalty through enhanced professionalism across all service dimensions.